Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.4018/ijpada.2020070101
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Disclosure as a Tool for Public Sector Legitimacy

Abstract: The purpose of this study is to measure the extent of Twitter environmental reporting by Andalusian municipalities (Spain) and identify the determinant factors of such a disclosure. Thus, factors such as population, geolocation, political signs, and sustainable commitments were analyzed under the legitimacy theory approach. The sample consisted of the official Twitter accounts of the 153 biggest local governments in Andalusia. The classification of the environmental tweets was based on a dictionary based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 81 publications
0
1
0
1
Order By: Relevance
“…Further, the values for P3, C3 and V3 indicate an accurate picture of how much the actual followers interacted on the Covid-19 Facebook posts. Bonsón et al (2020) found that government also uses social media platforms to promote their cities but not for CSR promotion. Similarly, profit-earning firms disseminate more information related to marketing rather than CSR.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Further, the values for P3, C3 and V3 indicate an accurate picture of how much the actual followers interacted on the Covid-19 Facebook posts. Bonsón et al (2020) found that government also uses social media platforms to promote their cities but not for CSR promotion. Similarly, profit-earning firms disseminate more information related to marketing rather than CSR.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…En todo caso, aunque la elaboración de memorias de sostenibilidad está poco extendida en la práctica de las entidades locales, numerosos trabajos dan cuenta de la divulgación de la información relativa a los aspectos sociales y medioambientales en la web, tanto en Europa (Navarro Galera et al, 2014) como en Australia (Hossain, 2018) y Latinoamérica (León-Silva et al, 2022), o incluso en las redes sociales (Bonsón et al, 2020); es decir que aunque no exista un informe específico o memoria de sostenibilidad estructurada, en algunos casos la información se proporciona en la web, pero muchas veces con contenidos inferiores a lo esperado. En ocasiones la ausencia de un marco normativo de referencia ha servido de argumento para su explicar su escasa generalización, aunque las entidades que han optado por elaborar informes de sostenibilidad han considerado las normas de la gri como referencia (Niemann y Hoppe, 2018).…”
Section: La Información De Sostenibilidad En El Sector Público: Situa...unclassified